Literacy Skills and Calculated 10-Year Risk of Coronary Heart Disease - Martin, Laurie T.; Schonlau, Matthias; Haas, Ann; Pitkin Derose, Kathryn; Rudd, Rima; Loucks, Eric B.; Rosenfeld, Lindsay; Buka, Stephen L. (Journal of general internal medicine : JGIM, 2011)
Background Coronary heart disease (CHD) is a leading cause of morbidity and mortality. Reducing the disease burden requires an understanding of factors associated with the prevention and management of CHD. Literacy skills may be one such factor. Objectives To examine the independent and interactive effects of four literacy skills: reading, numeracy, oral language (speaking) and aural language (listening) on calculated 10-year risk of CHD and to determine whether the relationships between literacy skills and CHD risk were similar for men and women. Design We used multivariable linear regression to assess the individual, combined, and interactive effects of the four literacy skills on risk of CHD, adjusting for education and race. Participants Four hundred and nine English-speaking adults in Boston, MA and Providence, RI. Measures Ten-year risk of coronary heart disease was calculated using the Framingham algorithm. Reading, oral language and aural language were measured using the Woodcock Johnson III Tests of Achievement. Numeracy was assessed through a modified version of the numeracy scale by Lipkus and colleagues. Key Results When examined individually, reading (p = 0.007), numeracy (p = 0.001) and aural language (p = 0.004) skills were significantly associated with CHD risk among women; no literacy skills were associated with CHD risk in men. When examined together, there was some evidence for an interaction between numeracy and aural language among women suggesting that higher skills in one area (e.g., aural language) may compensate for difficulties in another resulting in an equally low risk of CHD. Conclusions Results of this study not only provide important insight into the independent and interactive effects of literacy skills on risk of CHD, they also highlight the need for the development of easy-to use assessments of the oral exchange in the health care setting and the need to better understand which literacy skills are most important for a given health outcome.